Role of ehealth literacy, learning styles, and patterns of web-based e-content access for seeking health information among dental university students in Vadodara, India - Ramya R. Iyer; Rajesh Sethuraman (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Individual's learning style, ehealth literacy, and preferred web-based e-content and channel to access information determines how one makes sense of health information on the Internet. Understanding these dynamics will help design suitable e-contents and choose appropriate channels for effective health communication. To assess the relationship between ehealth literacy, learning styles, and web-based e-content accessed for receiving health information among dental college students in Vadodara, India. MATERIALS AND METHODS: A cross-sectional questionnaire study was conducted among all consenting Undergraduate Students (UGs), interns, and Postgraduate Students (PGs) of a dental college in Vadodara, India, from July to August 2022. The questionnaire used to collect data included questions on general information, eHealth literacy scale (eHEALS), Visual Auditory Reading/Writing Kinaesthetic (VARK) Questionnaire, and preferences of web-based e-content for receiving health information. Completely filled questionnaires were subject to statistical analysis: descriptive (means and percentages) and inferential (analysis of variance tests and odds ratio). RESULTS: 285 out of 380 students filled out the questionnaires completely (75% response rate). All reported using Internet for receiving health information. Majority preferred textual ehealth message (71%) and access websites (80%). Students were quadmodal (98.%) and trimodal (2%) learners who learned predominantly through kinaesthetic methods (46%). Mean eHEALS score of the group was 30.27 ± 3.41. There was a statistically significant association between preference for sharing channels and being a kinaesthetic learner (OR = 1.6; P = 0.04). CONCLUSIONS: Participants were multi-modal, predominantly kinaesthetic learners. The association between the preference for video-sharing channels and being kinaesthetic learner suggests the need and scope for demonstrative and interactive video-based health educational tools, with the endorsement of health authorities based on health policy.